A High Soldier Proportion Encouraged the Greater Antifungal Immunity in a Subterranean Termite - Zeng, Wenhui; Shen, Danni; Chen, Yong; Zhang, Shijun; Wu, Wenjing; Li, Zhiqiang (Frontiers in Physiology, 2022)
Termites possess a mighty social immune system, which serves as one of the key obstacles for controlling them biologically. However, the dynamic mechanism coordinating the social immunologic defense and caste distribution of the termites remains elusive. This study used the Coptotermes formosanus Shiraki and an entomopathogenic fungus as a host-pathogen system, and experimentally manipulated a series of groups with different caste compositions of workers and soldiers. It explored the impact of demography on the behavior and innate immunity of termites by analyzing the fungus-susceptibility of the respective caste, efficiencies, and caste preferences of sanitary care, as well as the expression of the immune gene and phenoloxidase activity. Overall, the infected workers were found to sacrifice their survivorship to maintain the soldier proportion of the group. If soldier-proportion was limited within a threshold, both the survivorship of the workers and soldiers were not significantly affected by infection. Correspondingly, within this threshold, the infected group with higher proportion of soldiers stimulated the higher efficiency of a no caste-biased sanitary care of the workers to the nestmate workers and soldiers. Moreover, the innate immunities of infected workers were found to be more intensely upregulated in the group with higher soldier-proportions. These suggested that the adjustable non-caste biased sanitary care and innate immunity of the worker would contribute to the flexibility of the worker-soldier caste ratio in C. formosanus. This study, therefore, enhanced our understanding of the functional adaptation mechanism between pathogen-drives social immunity and the demography of the termites.